Transgenerational epigenetic reprogramming of early embryos: a mechanistic model. Issue 1 (18th July 2020) - Spadafora, Corrado
Abstract: The notion that epigenetic information can be transmitted across generations is supported by mounting waves of data, but the underlying mechanisms remain elusive. Here, a model is proposed which combines different lines of experimental evidence. First, it has been shown that somatic tissues exposed to stressing stimuli release circulating RNA-containing extracellular vesicles; second, epididymal spermatozoa can take up, internalize and deliver the RNA-containing extracellular vesicles to oocytes at fertilization; third, early embryos can process RNA-based information. These elements constitute the building blocks upon which the model is built. The model proposes that a continuous stream of epigenetic information flows from parental somatic tissues to the developing embryos. The flow can cross the Weismann barrier, is mediated by circulating vesicles and epididymal spermatozoa, and has the potential to generate epigenetic traits that are then stably acquired in the offspring. In a broader perspective, it emerges that a natural 'assembly line' operates continuously, aiming at passing the parental epigenetic blueprint in growing embryos.